^{2}+bx+c=0 Multiply by 4a to get

^{2}x

^{2}+4abx+4ac=0 Compete the square as

^{2}=4a

^{2}x

^{2}+4abx+b

^{2}so that

^{2}x

^{2}+4abx+4ac=(2ax+b)

^{2}-b

^{2}+4ac=0

^{2}=b

^{2}-4ac

^{2}-4ac)

^{2}-4ac)

^{2}-4ac))/(2a)

how do we solve it

Tutors, sign in to answer this question.

Michael F. | Mathematics TutorMathematics Tutor

This answer comes from Littlewood's A University Algebra

ax^{2}+bx+c=0 Multiply by 4a to get

4a^{2}x^{2}+4abx+4ac=0 Compete the square as

(2ax+b)^{2}=4a^{2}x^{2}+4abx+b^{2} so that

4a^{2}x^{2}+4abx+4ac=(2ax+b)^{2}-b^{2}+4ac=0

(2ax+b)^{2}=b^{2}-4ac

2ax+b=±√(b^{2}-4ac)

2ax=-b±√(b^{2}-4ac)

x=(-b±√(b^{2}-4ac))/(2a)

Quadratic equation is derived by completing the square:

ax^2 + bx + c = 0

Subtract c from both sides:

ax^2 + bx = -c

Divide by a:

x^2 + (b/a)x = -c/a

Complete the square by taking half of b/a and squaring it, then adding to both sides:

Note: (b/a) * 1/2 = b/(2a)

x^2 + (b/a)x + (b/(2a))^2 = -c/a + (b/(2a))^2

Simplify:

x^2 + (b/a)x + b^2/(4a^2) = -c/a + b^2/(4a^2)

Factor:

(x - (b/(2a))))^2 = -c/a + b^2/(4a^2)

Take the square root:

x + (b/(2a)) = +/- sqrt(-c/a + b^2/(4a^2))

Subtract b/(2a) from both sides:

x = -b/(2a) +/- sqrt(-c/a + b^2/(4a^2))

Simplify:

x = -b/(2a) +/- sqrt( -4ac b^2 )

------- + ---------

4a^2 4a^2

x = -b +/- sqrt (b^2 - 4ac)

--------------------------

2a

Already have an account? Log in

By signing up, I agree to Wyzant’s terms of use and privacy policy.

Or

To present the tutors that are the best fit for you, we’ll need your ZIP code.

Your Facebook email address is associated with a Wyzant tutor account. Please use a different email address to create a new student account.

Good news! It looks like you already have an account registered with the email address **you provided**.

It looks like this is your first time here. Welcome!

To present the tutors that are the best fit for you, we’ll need your ZIP code.

Please try again, our system had a problem processing your request.